2021
DOI: 10.3389/fmars.2021.780268
|View full text |Cite
|
Sign up to set email alerts
|

Beta Diversity of Antarctic and Sub-Antarctic Benthic Communities Reveals a Major Role of Stochastic Assembly Processes

Abstract: Community assembly is the result of both, deterministic and stochastic processes. The former encompasses niche-based local-scale mechanisms such as environmental filtering and biotic interactions; the latter includes ecological drift, probabilistic colonisation, and random extinctions. Using standardised sampling protocols, we show that the spatial variation in species composition (beta diversity) of shallow subtidal macrobenthic communities of sub-Antarctic (Strait of Magellan and Yendegaia Fjord [Beagle Chan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 106 publications
(149 reference statements)
0
2
0
Order By: Relevance
“…Numerous studies have investigated the relative importance of stochasticity and determinism in different environments (e.g. Ellwood et al 2009, Caruso et al 2012, Shipley et al 2012, Ortega-Martínez et al 2020, Valdivia et al 2021). However, an understanding of the effects of land use change on the relative importance of stochastic and deterministic community assembly processes is largely absent, despite its potential importance.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have investigated the relative importance of stochasticity and determinism in different environments (e.g. Ellwood et al 2009, Caruso et al 2012, Shipley et al 2012, Ortega-Martínez et al 2020, Valdivia et al 2021). However, an understanding of the effects of land use change on the relative importance of stochastic and deterministic community assembly processes is largely absent, despite its potential importance.…”
Section: Introductionmentioning
confidence: 99%
“…Determinism and stochasticity are opposite ends of a continuum, with real‐world communities existing somewhere between these extremes (Gravel et al 2006, Kitching 2013). Previous studies have investigated the balance between stochasticity and determinism in different environments (Ellwood et al 2009, Caruso et al 2012, Shipley et al 2012, Ortega‐Martínez et al 2020, Valdivia et al 2021), but few have addressed the impact of land use change on this balance, despite the potential importance of this. It is often suggested that community assembly processes exhibit hysteresis (Beisner et al 2003), implying that restoring an ecological community in a modified habitat could rely on different assembly processes than those that exist in primary habitats (Andersen et al 2009, Suding and Hobbs 2009).…”
Section: Introductionmentioning
confidence: 99%